Review: regulatory mechanisms of gonadotropin-inhibitory hormone (GnIH) synthesis and release in photoperiodic animals - Tsutsui, Kazuyoshi; Ubuka, Takayoshi; Bentley, George E.; Kriegsfeld, Lance (Frontiers in Neuroscience, 2013)
Gonadotropin-inhibitory hormone (GnIH) is a novel hypothalamic neuropeptide that was discovered in quail as an inhibitory factor for gonadotropin release. GnIH inhibits gonadotropin synthesis and release in birds through actions on gonadotropin-releasing hormone (GnRH) neurons and gonadotropes, mediated via the GnIH receptor (GnIH-R), GPR147. Subsequently, GnIH was identified in mammals and other vertebrates. As in birds, mammalian GnIH inhibits gonadotropin secretion, indicating a conserved role for this neuropeptide in the control of the hypothalamic-pituitary-gonadal (HPG) axis across species. Identification of the regulatory mechanisms governing GnIH expression and release is important in understanding the physiological role of the GnIH system. A nocturnal hormone, melatonin, appears to act directly on GnIH neurons through its receptor to induce expression and release of GnIH in quail, a photoperiodic bird. Recently, a similar, but opposite, action of melatonin on the inhibition of expression of mammalian GnIH was shown in hamsters and sheep, photoperiodic mammals. These results in photoperiodic animals demonstrate that GnIH expression is photoperiodically modulated via a melatonin-dependent process. Recent findings indicate that GnIH may be a mediator of stress-induced reproductive disruption in birds and mammals, pointing to a broad role for this neuropeptide in assessing physiological state and modifying reproductive effort accordingly. This paper summarizes the advances made in our knowledge regarding the regulation of GnIH synthesis and release in photoperiodic birds and mammals. This paper also discusses the neuroendocrine integration of environmental signals, such as photoperiods and stress, and internal signals, such as GnIH, melatonin and glucocorticoids, to control avian and mammalian reproduction.